Under the Radar: American Universities Abroad - Long, Kyle; Panangipalli, Saiansha (International Higher Education, 2023)
Conventional wisdom about American campuses abroad suggests that they are typically vanity projects for cosmopolitans. This view reflects only a partial reality. A new database from the Global American Higher Education initiative shows that the landscape is more diverse and inclusive than commonly understood. These institutions are largely unknown in the United States but extend the American higher education footprint into 80 countries around the world.